Structural, magnetic and magnetocaloric properties of Ag-doped Pr0.5Sr0.5-xAgxMnO3 manganites (0.0≤x≤0.4). Issue 1 (January 2017) - Tarhouni, S.; Mleiki, A.; Chaaba, I.; Ben Khelifa, H.; Cheikhrouhou-Koubaa, W.; Koubaa, M.; Cheikhrouhou, A.; Hlil, E.K.
Abstract: The effects of partial silver substitution on the structural, magnetic and magnetocaloric properties of Pr0.5 Sr0.5- x Ag x MnO3 (0.0≤ x ≤ 0.4) compounds have been studied. Our powder specimens are synthesized using the sol-gel method at high temperatures. X-Ray diffraction study reveals that all compounds crystallize in the distorted orthorhombic symmetry with Pbnm space group. Magnetization measurements versus temperature under 0.05 T reveal the presence of an antiferromagnetic (AFM) to ferromagnetic (FM) transition at low temperatures for the parent compound, followed by a second one from FM to paramagnetic state (PM). Ag doping is found to reinforce the FM behavior with a Curie temperature (TC ) increasing from 268 ( x =0.0) to 305 K( x =0.2). However, for higher Ag amount, TC decreases again from 285 K ( x =0.3) to 170 K ( x =0.4). The maximum of the magnetic entropy change ( - Δ S M m a x ) was calculated using the isothermal magnetization curves M (H) under magnetic field change of 5 T and is found to be 4.7 J/(kg K) for x =0.3. The relative cooling power (RCP) turns out to be 188 J/kg and 229 J/kg for x =0.0 and x =0.1, respectively. This suggests that these compounds may be suitable candidates for magnetic refrigeration.